Criminal justice in England and the United States - Hirschel, Joseph David (Criminal justice illuminated, 2008)
An introduction to comparative criminal justice research -- The English cultural heritage and government system -- English criminal law -- The English crime problem -- The history and organization of the police -- The modern english police -- The criminal courts, judges, and lawyers -- The court process -- The development of confinement and corrections in England -- The organization and operations of corrections -- Terrorism (new chapter) -- Juvenile justice in England (new chapter) -- Conclusion